A portable micro glucose sensor based on copper-based nanocomposite structure. (8th May 2019) - Chen, Huang; Fan, Guokang; Zhao, Jie; Qiu, Meijia; Sun, Peng; Fu, Yifeng; Han, Dongxue; Cui, Guofeng
Abstract : A sensor device based on a copper-based nanocomposite structure is achieved and presents excellent sensing performance for glucose. Abstract : Precisely detecting the concentration of glucose in the human body is an attractive way to prevent or treat diabetes. Portable glucose sensors with non-enzymatic catalytic materials have received great attention in recent years. Herein, a facile strategy for fabricating a high-performance electrochemical sensor is proposed. A non-enzymatic three-electrode integrated glucose sensor device based on CuO nano-coral arrays/nanoporous Cu (NCA/NPC) is designed and fabricated. The portable NCA/NPC glucose sensor device exhibits high catalytic activity for glucose. The great performance of the NCA/NPC glucose sensor device derives from the excellent conductivity of the NPC substrate and the high electrocatalytic activity of CuO nano-coral arrays. This device exhibits a high sensitivity of 1621 μA mM −1 cm −2 in the linear range of 0.0005–5.0 mM, low detection limit of 200 nM (S/N = 3), fast response time of 3 s, good anti-interference performance, excellent repeatability and considerable stability for glucose detection. This work will certainly provide an efficient structure and proper catalytic material choices for future non-enzymatic glucose sensors.